Strain-Compensated Quantum Well Asymmetric Waveguide Edge-Emitting Laser Operating at 730 nm - Lutai Fan; Lijie Cao; Peng Jia; Qian Liu; Baiheng Liu; Haofei Chen; Yongyi Chen; Li Qin; Lei Liang; Yuxin Lei; Cheng Qiu; Yue Song; et al. (Sensors)
Semiconductor lasers operating at the 730 nm peak wavelength have diverse applications, including biomedical diagnostics, agricultural lighting, and high-precision sensing. However, quantum well (QW) materials, commonly employed at this wavelength, often fail to simultaneously meet the dual requirements of lattice matching and bandgap alignment. In this study, GaAsP/AlGaInP large strain compensation QW with lattice mismatches of −7.533‰ and 1.112‰ was developed. Strain compensation was utilized to address the lattice mismatch while ensuring lasing action at 730 nm. Based on this, the impact of waveguide design, particularly graded and asymmetric waveguides, on the power output was explored. Additionally, the relationship between the doping profile of the device and lasing efficiency was investigated. The completed 100 μm wide semiconductor edge-emitting laser (EEL) achieved 730 nm continuous wave laser with 1 W output power at 2 A current. This study proposes an approach to enhance the lasing power and optoelectronic conversion efficiency of lasers and provide valuable solutions for their practical applications.